2005
DOI: 10.1063/1.2147708
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced higher-harmonic imaging in tapping-mode atomic force microscopy

Abstract: Cataloged from PDF version of article.Higher-harmonics generation in a tapping-mode atomic force microscope is a consequence of the nonlinear tip-sample interaction force. The higher harmonics contain important information about the materials’ nanomechanical properties. These harmonics can be significantly enhanced by driving the cantilever close to a submultiple of its resonant frequency. We present the results of enhanced higher-harmonic imaging experiments on several samples. The results indicate that enhan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
17
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 15 publications
0
17
0
Order By: Relevance
“…Also, by enhancing and exploiting the dynamics of the higher harmonics, the resolution of AFM can be enhanced [2,3,15,21]. Stark showed [20,22] that the higher harmonics cannot be neglected in the analysis of the tapping-mode AFM.…”
mentioning
confidence: 97%
“…Also, by enhancing and exploiting the dynamics of the higher harmonics, the resolution of AFM can be enhanced [2,3,15,21]. Stark showed [20,22] that the higher harmonics cannot be neglected in the analysis of the tapping-mode AFM.…”
mentioning
confidence: 97%
“…4 Thus, in an attempt to access the tip-sample interaction which can be quantitatively related to the material properties, the higher-order harmonic components in the vibration spectrum of the tapping cantilevers have attracted particular attention in the recent years. [5][6][7][8][9][10] A more detailed imaging with a better contrast which reveals the variation in material properties was obtained with the higher-harmonic resonance signal than that with the fundamental one, [11][12][13] while theoretical investigations and numerical simulations revealed that the high-order harmonic components contain the information on elastic properties of the sample surface. 7,9,13 The high force sensitivity of higher harmonics or modes has been quantitatively examined by Lozano and Garcia.…”
mentioning
confidence: 99%
“…3,12 While the cantilever is excited at or near its fundamental natural frequency to ensure a high-sensitive signal output of vibration amplitudes mainly corresponding to the fundamental eigenmode during the topography imaging, signal contributions from the higher harmonics of vibration amplitude are usually suppressed by the rapid decay of the frequency response curve of a continuum cantilever. 15 In fact, the frequency response curve only exhibits high peaks near the natural frequencies corresponding to each of the vibration eigenmodes, as shown in Fig.…”
mentioning
confidence: 99%
“…A great number of efforts have been made to enhance the higher harmonic signals. The higher harmonics are enhanced by simultaneously exciting the first two modes of a cantilever, 14 or by driving the cantilever around a submultiple of the fundamental frequency, 8,15 or by exciting the torsional modes in a torsional harmonic cantilever. 16 Besides excitation, the geometry of cantilever can also be modified to enhance its response.…”
mentioning
confidence: 99%